Reagent Preparation: Theoretical and Practical Discussions. Issue 9 (28th October 2014) - Chakravarti, Deb N.; Chakravarti, Bulbul; Mallik, Buddhadeb
Abstract: One of the most important requirements for success with any biochemical protocol is the accurate preparation of reagents. This unit provides general guidelines for the preparation of reagents, including use of clean glass‐ and plasticware, use of high‐purity reagents, safe handling of chemicals and biochemicals, use of high‐purity distilled or deionized water, and avoidance of chemical or microbial contamination. Different units of concentration used for preparation of reagents or buffer solutions are described. This unit also includes a section for the preparation of buffer solutions with a practical example. © 2014 by John Wiley & Sons, Inc.